Schooling without labels : parents, educators, and inclusive education - Biklen, Douglas (Health, society, and policy., 1992)
"By closely examining the experiences of six families whose children with disabilities are full participants in family life, Douglas Bilken shows how people who have been labeled disabled might become full participants in other areas of society as well. Biklen focuses on the contradictions between what some families have achieved, what they want for their children, and what society and its social policies allow. He demonstrates how the principles of inclusion that govern the lives of these families can be extended to education, community life, and other social institutions." "The parents who tell their stories here are not typical. All have actively sought their children's inclusion in regular schools and community settings; several have children with severe or multiple disabilities. They are determined, combative, and resilient people, whose narratives show the love, pride, and respect they feel for their children. In disussing issues such as normalization, acceptance, complete schooling, circles of friends, and community integration, these parents describe the challenge and need for their children to "lead regular lives." Biklen observes that being identified as disabled and receiving increased attention has not necessarily resulted in greater options for students or their parents or more control over their destinies." "The author addresses the concept of disability and describes how labels damage people. He asks: How would society have to alter its values, its notion of excellence, its evaluation of individuals, its language, its forms of mutual support, in order to adopt the vision that a person with disabilities is a full participant in everyday life? Schooling without Labels challenges our notions of "normal," and "handicapped" as well as our notion of "education.""--Jacket